Torrefaction of tea brewing waste pellets and investigation of their pyrolysis properties under isothermal conditions by macro-TGA approach - Duranay, Neslihan; Yildiz, Gulsah; Tasar, Seyda; Yilgin, Melek (Taylor & Francis Inc, 2025)
This study examines the torrefaction of tea-brewing waste (TBW) in pellet form to assess its suitability as a biochar precursor. Torrefaction experiments were carried out over periods of 30 and 60 min. in a fixed-bed reactor under an inert nitrogen atmosphere, maintaining a flow rate of 100 ml.min-1 at temperatures of 200 degrees C, 250 degrees C, and 300 degrees C. We investigated the impact of torrefaction conditions on energy yield (EY), higher heating value (HHV), and the yield of the solid product. The pyrolysis of both raw TBW and torrefied samples (TS) was modeled using macro-TGA in a static atmosphere. Isothermal pyrolysis kinetics were analyzed through the Coast-Redfern (CR) method to elucidate the thermal degradation behavior and underlying reaction mechanisms. The HHV of torrefied samples varied between 23.29 MJ.kg-1 and 27.08 MJ.kg-1 under conditions of 250 degrees C for 30 min. and 300 degrees C for 60 min. Concurrently, the O/C and H/C atomic ratios diminished as both the temperature and duration of the process increased. The chemical kinetics F(3) model, indicative of a third-order reaction where the reaction rate is proportional to the cube of the remaining reactant concentration, yielded the most precise depiction of thermal degradation. The activation energy and frequency factor for raw TBW were established at 31.29 kJ.mol-1 and 17 s-1, respectively. Thermodynamic parameters Delta H, Delta G, and Delta S were calculated to be 25.27 kJ.mol-1, 62.75 kJ.mol-1, and -0.049 kJ.mol-1K-1, respectively, confirming the endothermic nature of the pyrolysis process. These values suggest a trend toward spontaneous occurrence and a reduction in product disorder relative to the reactants.
Keywords: Tea-brewing waste; pellet; torrefaction; macro-TGA; pyrolysis; kinetic